A method of sharing a secret key in quantum key distribution - Wan Adnan, Wan Azizun; Ahmad Ghazali, Lizal Iswadi; Abas, Ahmad Fauzi; Mokhtar, Makhfudzah; Mahdi, Mohd Adzir; Saripan, M. Iqbal (2010)
A method of sharing a secret key in quantum key distribution during basis reconciliation of decoding is provided, characterized in that, the method includes the steps of comparing a received pair state at a first stage whether said received pair state is orthogonal to a transmitter pair state (209), comparing a received pair state at a second stage whether said received pair state is orthonormal to a transmitter pair state (211),wherein a received pair state is orthogonal to the transmitted pair state, therefore an unused component of the pair state is converted to a classical value and shared as a secret key bit (215).